(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Reversed-phase ultra-performance liquid chromatography (RP-UPLC) is a powerful analytical technique widely employed in the pharmaceutical field. This article reviews the principles, advantages, and limitations of RP-UPLC, alongside its various applications in drug development, quality control, and bioanalysis. The growing significance of this technique in ensuring the efficacy and safety of pharmaceutical products is highlighted, along with future perspectives in the context of advancing analytical technologies.